National and Cultural Specificity of the Associative Fields of the Uzbek and Russian Languages - Khamraeva Yorkinoy Nabijanovna (International Journal on Integrated Education, 2026)
This article is devoted to the study of the national-cultural characteristics of fields in a broad linguocultural and psycholinguistic context. The main goal of the study is to identify similarities and differences in the associative reactions of representatives of the two languages, as well as to reveal their cultural values, mentality and national thinking expressed through language. The study used free associative experiment, semantic analysis, statistical processing and linguocultural interpretation methods based on a comparative-descriptive approach. Associative fields were formed on the basis of socially and culturally significant stimulus words and analyzed according to their semantic groups and national-cultural signs. The results showed that family, collectivism, tradition, respect and moral values occupy a leading place in associative fields in the Uzbek language. In the Russian language, associations focused on individuality, abstract concepts and socio-political phenomena prevail. Although both languages have universal associations inherent in all people, their cultural interpretation is manifested differently. In conclusion, associative fields serve as an important indicator in determining the national mentality and cultural identity, and comparative research of the Uzbek and Russian languages serves to deepen intercultural dialogue.